Association Between Institutional Factors and Long‐Term Survival Following Transjugular Intrahepatic Portosystemic Shunt. Issue 6 (25th March 2019) - Mah, Jeffrey M.; DeWit, Yvonne; Djerboua, Maya; Menard, Alexandre; Booth, Christopher M.; Flemming, Jennifer A.
Abstract : Transjugular intrahepatic portosystemic shunt (TIPS) is a procedure designed to treat portal hypertension. Hospital teaching status is an institutional factor found to be predictive of outcomes following several complex procedures; however, its impact on outcomes following TIPS is unknown. The aim of this study was to determine the association between hospital teaching status and long‐term survival in patients with cirrhosis receiving TIPS. We performed a retrospective population‐based cohort study using linked administrative health data from Ontario, Canada. Adult patients with cirrhosis who received TIPS between January 1, 1998, and December 31, 2016, with follow‐up until December 31, 2017, were included. Hospital teaching status was defined based on hospital participation in the instruction of medical students and/or resident physicians. Liver transplant‐free (LTF) survival was evaluated using Kaplan‐Meier analysis, and overall survival was assessed using competing risks regression analysis, which accounted for hospital clustering. A total of 857 unique patients were included (mean age 57.1 years; 69.1% male). The TIPS procedures were performed in teaching hospitals (84.3%) as well as nonteaching hospitals (15.7%). Median LTF survival was more than twice as long for procedures performed in teaching hospitals compared to nonteaching hospitals (2.2 years versus 0.9 year, respectively; P < 0.001). After adjusting for confounders and clustering, hospital teaching status was not independently associated with mortality (nonteaching subdistribution hazard ratio [sHR], 1.32; 95% confidence interval [CI], 0.97‐1.81; P = 0.08); however, annual hospital procedure volume was (per unit increase sHR, 0.96; 95% CI, 0.93‐0.99; P = 0.003). Conclusion: Hospital procedure volume is associated with long‐term survival following TIPS. These results further support the centralization of TIPS to high‐volume hospitals to improve long‐term outcomes in this population. Abstract : The association between hospital teaching status, procedural volume and long‐term outcomes post‐TIPS are not known. In this population‐based study from Ontario, Canada, hospital teaching status was not associated with long‐term survival however, hospital procedural volume was. Our results support future research focusing on the centralization of TIPS to high volume centers of excellence to improve long‐term outcomes in this population.